Role-Playing as a tool for improving ESL Learners’ communication skills: a systematic review - Vaishnu Rao Kumara Rao,; Nur Yasmin Khairani Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Role-playing in the classroom allows students to simulate scenarios or take on different roles to enhance their communication skills. Communication is often considered the most challenging language skill to master, compared to reading and writing. This study conducts a systematic review of 25 relevant studies published between 2011 and 2023 from sources including Google Scholar, Research Gate, Semantic Scholar, Academia, SAGE, ProQuest, HRMAS, JELTL, and the Educational Resources Information Centre (ERIC) database. The aim is to assess the effectiveness of role-playing in improving ESL students’ communication skills. The findings reveal that role-playing significantly enhances students’ speaking abilities, particularly in terms of fluency, comprehension, contextual understanding, and interactive skills. Additionally, role-playing increases students’ confidence in communicating in English and encourages more frequent use of English in the classroom. Future research should explore long-term effects of role-playing and its impact on different proficiency levels. Practical applications include integrating role-play activities into ESL curricula to foster a more interactive learning environment. However, limitations of existing studies include small sample sizes and a lack of longitudinal research.